Lute como uma gorda : gordofobia, resistências e ativismos - Jimenez Jimenez, Maria Luisa (2020)
Taking into account the debate about female fat bodies, marked by the socially standardized discourse, in which thinness is the prevailing canon. When a body is not within this standard, that is, a thin body that is considered as beautiful and healthy, is stigmatized, being considered ugly, bad, abnormal, sick, weak and sad, and therefore socially excluded. This discrimination is known as fatphobia, a prejudice that leads to social exclusion and denies accessibility to fat people. This stigma is structural and cultural, broadcast in many diverse areas and social contexts in contemporary society. The aim of this thesis is thus unravel the fat in the contemporary world, to analyze how these bodies are designed institutionally, and how those fat women themselves perceive, accept or resist gordofobia. To achieve this goal, the author uses self-ethnography, everyday sociology, consumer studies, feminism, and netnography. As a starting point of the research, the testimonies of fat women in collectives, conversations, the internet, memory and her own experiences as a fat woman, direct analysis and writing through three subthemes: daily life, consumption and activism, which point out that despite being fattened to fat bodies, many of them have positioned themselves against gordophobia, organized into collectives, cyberspace and on the streets to show that female fat bodies can overcome this recrimination, resisting the current conception of the only possible body, which in our society is being skinny. We build a different episteme on fat bodies and propose the resistance, in which a political body breaks patterns and puts itself in the world in a creative and joyful way.